Results of the multicenter, prospective, randomised STRENGTH (Study To evaluate the use of RENalGuard to proTect patients at High risk of acute kidney injury) study. (25th November 2020) - Garot, P; Sievert, H; Mahfoud, F; Carrie, D; Lipiecki, J; Nickenig, G; Remppis, A; Eckert, S; Fajadet, J; Morice, M.C
Abstract: Aim: Radio-contrast agents are widely used in coronary, peripheral and structural interventions. Use of these iodine-containing agents can be associated with contrast-induced acute kidney injury (CI-AKI) that can cause substantial morbidity and mortality. The RenalGuard system induces a forced diuresis with a matched hydration and has been shown beneficial in patients requiring coronary angiogram and PCI. Methods: STRENGTH is a prospective, randomised (1:1), open-labeled, parallel-group, multicenter (10 centers in Germany and France) study where patients at high risk of CI-AKI were randomly assigned to RenalGuard® therapy or conventional strategy including preventive hydration before complex percutaneous cardiovascular intervention (PCI, peripheral and structural). In the RenalGuard arm, matched fluid replacement was started 60 minutes pre-procedure and maintained for up to 4 hours afterwards. Patients were given an initial i.v. bolus of up to 250 ml of normal saline over 30 minutes and then an i.v. bolus of furosemide (0.5 mg/kg). To be enrolled, patients had to have moderate to severe renal failure (defined as 15≤eGFR≤40 mL/min/m 2 ) and a high-volume contrast requiring cardiovascular procedure (estimated contrast volume>3 times eGFR value). The main exclusion criterion was administration of iodine contrast media within 5 days before index procedure. The primary endpoint was CI-AKI defined as an increase in sCr ≥0.3 mg/dL or an increase of 25% of basal value or requiring dialysis within 5 days after procedure. The primary analysis for efficacy is performed in a modified intention-to-treat basis. The trial was designed and monitored by an independent CRO (Cardiovascular European Research Center, CERC, Massy, France). Results: A total of 259 patients aged 79.1±8.8 yrs were included in the study. Among them, 129 were assigned to RenalGuard therapy and 130 to preventive saline hydration. Their mean baseline eGFR was 32 (25; 37) vs. 33 (25; 39) mL/min/m 2, respectively (p=0.88). Total fluid intake volume within 24hrs before the procedure was 2383±1146 vs. 1386±842mL, respectively (p<0.0001). Procedure type was complex PCI (48%), TAVI (25%), peripheral intervention (18%), other structural intervention (9%) with no difference between groups (p=0.56). The total amount of contrast used for the procedure was 116.3±68.2mL in the RenalGuard arm vs. 104.1±56.7 mL in the conventional arm (p=0.26). A staged procedure was performed in 24 patients, including 16 in the RenalGuard and 8 in the control arm with a mean interval from the first intervention of 43±29 days and 24±19 days, respectively. For this second procedure, the total amount of contrast was 80±59 vs. 87±73mL. Conclusion: The primary and secondary endpoints of the Study To evaluate the use of RENalGuard to proTect patients at High risk of CI-AKI comparing RenalGuard therapy to conventional hydration in 259 patients requiring complex percutaneous cardiovascular intervention will be presented. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): CERC